Release of bound aliphatic biomarkers via hydropyrolysis from Type II kerogen at high maturity - Lockhart, Robert; Meredith, W.; Love, G.; Snape, C. (Pergamon, 2008)
At relatively low maturity, kerogen-bound aliphatic biomarkers invariably display retardedmaturity compared to their ‘‘free” counterparts as a result of the protection afforded by themacromolecular structure. This study investigates the release of hopanes and steranes atelevated (post oil window) maturity from Type II kerogen. Results for a suite of NorthSea petroleum source rocks (Kimmeridge Clay Formation) indicate that, below a hydrogenindex (HI) value of ca. 300, differences between the ‘‘free” and ‘‘bound” phases for hopaneand sterane side chain isomerisation are small. However, ring isomerisation within the kerogen-bound phase is still more retarded. For a corresponding series of kerogen samplesartificially matured via hydrous pyrolysis, both ‘‘free” and ‘‘bound” phase side chain isomerisationreactions are significantly retarded relative to the naturally occurring samples.This is consistent with earlier studies, but the extent of retardation for ring isomerisationin the ‘‘bound” phase is even more pronounced than for the ‘‘free” phase.